Transatlantic differences in labour markets changes in wage and non-employment structures in the 1980s and the 1990s - Patrick A. Puhani (Technische Universität Darmstadt, Department of Law and Economics, 2005)
Rising wage inequality in the U.S. and Britain and rising continental European unemployment have led to a popular view in the economics profession that these two phenomena are related to negative relative demand shocks against the unskilled, combined with flexible wages in the Anglo-Saxon countries, but wage rigidities in continental Europe ('Krugman hypothesis'). This paper tests this hypothesis based on seven large person-level data sets for the 1980s and the 1990s. I use a more sophisticated categorisation of low-skilled workers than previous studies, which highlights the distinction between German workers with and without apprenticeship training. I find evidence for the Krugman hypothesis when Germany is compared to the U.S. However, supply changes differ considerably between countries, with Britain experiencing enormous increases in skill supply explaining the relatively constant British skill premium in the 1990s.
Keywords: J21; J31; J64; 330; wage; earnings; unemployment; non-employment; rigidity; identification; Arbeitsmarkt; Lohnrigidität; Ungelernte Arbeitskräfte; Lohnstruktur; Vergleich; USA; Großbritannien; Deutschland